The insecure future of the World Economic Growth - NIELSEN, Ron W. (Turkish Economic Review, 2025)
Growth rate of the world Growth Domestic Product (GDP) is analysed to determine possible pathways of the future economic growth. The analysis is based on using the latest data of the World Bank and it reveals that the growth rate between 1960 and 2014 was following a trajectory approaching asymptotically a constant value. The most likely prediction is that the world economic growth will continue to increase exponentially and that it will become unsustainable possibly even during the current century. A more optimistic but less realistic prediction is based on the assumption that the growth rate will start to decrease linearly. In this case, the world economic growth is predicted to reach a maximum, if the growth rate is going to decrease linearly with time, or to follow a logistic trajectory, if the growth rate is going to decrease linearly with the size of the world GDP. Keywords. Economic growth; World economic growth; Gross Domestic Product; Predicting future growth; Exponential growth. JEL. C01; C20; C50; C53; C60; C65; C80.